A randomised controlled trial comparing the efficacy of micellised and fat-soluble vitamin D3 supplementation in healthy adults. Issue 8 (22nd March 2019) - Marwaha, Raman K.; Dev, Tanvi; Mittal, Ambrish; Mani, Kalaivani; Narang, Archna; Arora, Preeti; Singh, Anne; Chadha, Aditi; Dang, Navin; Goel, Meetu; Sharma, Vinod K.; Sethuraman, Gomathy
Abstract: Nanoemulsion formulation of vitamin D3 have been shown to have better bioavailability than the coarse emulsion preparation in vitro and in vivo animal studies. In the absence of randomised trial in humans, comparing the efficacy of nanotechnology-based miscellised vitamin D3 over conventional vitamin D3, we undertook this study. A total of 180 healthy adults were randomised to receive either micellised (DePura, group A) or conventional vitamin D3 (Calcirol, group B) at a monthly dose of 60 000 IU (1500μg) for 6 months. The outcome parameters were serum 25 - hydroxyvitamin D (25(OH)D), parathyroid hormone (PTH), Ca, phosphate, alkaline phosphatase and urinary Ca:creatinine ratio. A total of eighty-nine subjects in group A and seventy-seven in group B completed the trial. Subjects in both the groups had a significant increase in their serum 25(OH)D levels following supplementation (group A: 21·5 (sd 10·9) to 76·7 (sd 18·8) nmol/l ( P <0·001); group B: 22·8 (sd 10·4) to 57·8 (sd 16·0) nmol/l ( P <0·001)). Participants in micellised group had an additional increase of 20·2 (95 % CI 14·0, 26·4) nmol/l in serum 25(OH)D levels ( P <0·001). The difference between the groups was 17·5 (95 % CI 11·8, 23·1) nmol/l, which remained statistically significant ( P <0·001) even after adjustment for age and sex. Significant decline in mean serum PTH was observed in both the groups. No hypercalcaemia or hypercalciuria was noted. Although supplementation with both the preparations resulted in a significant rise in serum 25(OH)D levels, micellised vitamin D3 appeared to be more efficacious in achieving higher levels of serum 25(OH)D.